Association of endothelial nitric oxide synthase gene polymorphisms with end-stage renal disease: a systematic review and meta-analysis. (July 2014) - Yun, Zhu; Yu-Ping, Yang; Zong-Wu, Tong; Yang, Sun; Fang, Yang; Fang, Sun
Abstract Background and objective: Endothelial nitric oxide synthase (eNOS) is one of the potent regulators of intra renal hemodynamics. Polymorphisms of eNOS gene may be involved in the progression of renal disease, and may be the causative factors that contribute to the deterioration of renal functions. During the past decades, several studies investigated the association of eNOS polymorphisms with the risk of end-stage renal disease (ESRD), but the results remain unclear and the mechanisms are not defined. Our study was designed to examine the role of different eNOS genetic polymorphisms in the progression of ESRD. Materials and methods: Relevant studies were identified through PubMed, Embase, Medline and CNKI (China National Knowledge Infrastructure) database published between January 2000 and November 2013. The association between eNOS polymorphisms and ESRD susceptibility was assessed by pooled odds ratios (ORs) and 95% confidence intervals (95% CI) in fixed or random effects models. Results: Sixteen articles were identified for the analysis of association between eNOS gene polymorphisms and ESRD risk. A total of 2729 patients and 2190 controls for 4b/a, 851 patients and 1171 controls for G894T, and 513 patients and 487 controls for T786C were included in our analysis. Overall, 4a allele of 4b/a polymorphism produced a significant association in the global population (OR = 1.47, 95% CI = 1.05–2.06, p = 0.03) in a random-effect model; T allele of G894T was also significantly associated with ESRD susceptibility in overall populations (OR = 2.12, 95% CI = 1.44–3.12, p = 0.0001). Furthermore, 4a and T carriers were significantly associated with ESRD risk as well. No association was found between T786C polymorphism and ESRD. Conclusion: The evidence accumulated suggested that 4b/a and G894T polymorphisms in the eNOS gene were associated with ESRD susceptibility, indicating that 4a and T allele carriers might become significant genetic molecular markers for the onset of ESRD in overall populations. However, more studies should be performed in the further studies.